Gastric fundus leiomyoma: a rare case report - Kaiyuan Luo; Jianfeng Bin; Jun Bian; Haomin Wang; Dai Tang; Maozhao Yan; Hua Ge (Frontiers in Oncology)
BackgroundGastric leiomyoma is a rare, slow-growing benign tumor originating from the smooth muscle cells of the gastric wall. It is typically asymptomatic and presents insidiously. Due to its clinical and imaging features resembling those of gastrointestinal stromal tumors and other gastric neoplasms, it is often misdiagnosed, leading to unnecessary surgical interventions. This article reports a case of gastric leiomyoma in a 28-year-old male, aiming to explore its diagnosis, differential diagnosis, and treatment strategies, emphasizing the importance of comprehensive preoperative imaging evaluation to provide a reference for clinical practice.Case presentationA 28-year-old male underwent gastroscopy due to abdominal pain, which revealed a submucosal protrusion in the gastric fundus. Imaging studies (computed tomography, endoscopic ultrasonography, and magnetic resonance imaging) showed a round-like mass approximately 6.3 cm in diameter in the gastric fundus, with mixed internal echogenicity. The patient underwent laparoscopic resection of the gastric fundus tumor, during which the tumor was completely excised. Postoperative pathological and immunohistochemical results confirmed the diagnosis of gastric leiomyoma. The patient recovered well and was discharged one week after surgery.ConclusionsThe diagnosis of gastric leiomyoma requires a combination of imaging, pathological, and immunohistochemical findings to differentiate it from other gastric tumors such as gastrointestinal stromal tumors. Preoperative comprehensive analysis using computed tomography, magnetic resonance imaging, and endoscopic ultrasonography can improve diagnostic accuracy. For gastric leiomyoma, tumor resection with preservation of the cardia is an ideal surgical approach, ensuring negative margins while reducing postoperative complications (anastomotic stenosis). The successful treatment of this case provides a reference for the diagnosis and surgical management of gastric leiomyoma, contributing to improved patient prognosis and quality of life.